ANALISIS POTENSI SUMBER DAYA KAWASAN TRANSMIGRASI DAN KAWASAN INDUSTRI PERKOTAAN BARU BUMI ASRI DUSUN TANGAH UNTUK MEMPERCEPAT PEMBANGUNAN SOLOK SELATAN SEBAGAI DAERAH TERTINGGAL DI SUMATERA BARAT - Kardiman Kardiman (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2019)
Analysis of the structure and utilization of the area is done by observing and assessing the structure and utilization of the area, both in the present, past, and future trends, but within the internal scope of the region. Determination of city order, service area scale, and structuring of districts to be more effective and efficient is a goal obtained from the analysis of this aspect. This research has a goal that is to determine the leading sector and re-gional development strategy in order to alleviate poverty and formulate an inte-grated concept for South Solok regency out of the category of disadvantaged areas in 2019. The research method used is surveyed approach with analytical tool is Lo-cation Quotient (LQ) and spatial analysis, planning area structure following poli-cy which has been outlined by RTRWN, RTRWP, and RTRW; the position and scale of the system of movement, concentration of activities, and allotment of land; The direction of development of regional development; taking into account the physical characteristics and carrying capacity of the environment and asso-ciated with the level of vulnerability to disasters. The research location is in South Solok District. The results showed that there were 5 leading sectors with LQ> 1 value ie agriculture, forestry and fishery sector, mining and quarrying sector, construction sector, trade, and retail; car and motorcycle repairs, health services and social activities. Of the five leading sectors, the sector that has the greatest advantage is the mining and quarrying sector which has LQ value exceeding 2 means, this sec-tor has twice the prospect of the same sector throughout West Sumatra, and the next is the Agriculture, Forestry and Fisheries sector with the value of LQ reached 1.4, meaning that this sector has a 1.4 times greater advantage than the same sector throughout West Sumatra. Another sector that has advantages is the Big trading sector with a value of LQ 1.24, meaning that the Greater Wholesaler and Trade Center has a good prospect for the future development of the KPB-BAD Trade and Business Center. On the other hand, there are two main commodity groups in agriculture, forestry and fishery sector in RKT KPB area, firstly Commodity Perak-bunan (Rubber, Palm Oil, Cocoa) which have LQ value of 1.33, meaning that plantation sector is more than 1.33 times than other commodities in this sector compared to other regions in West Sumatra province, in addition to food crop commodities al-so have a value of 1.02 LQ, which means above average compared to other com-modities in West Sumatra Province. Second, commodities with good prospects are livestock commodities with LQ = 1. 2 The concept of development that can be offered for South Solok to come out from underdeveloped and developed areas is by planning the development of Transmigration Area as hinterland area is integrated with the planning of new urban area as the industrial center (Value Added Centre). The farmers in the study area 3 Sangir Jujuan subdistrict, Sangir Balai Janggo subdistrict, Sangir Batang Hari subdistrict are farmers with narrow land category with the average land area of 0.6 Ha per person with the population of 48,949 people, so in the planning it is needed hard effort to create field (agro-industry, services and trade, mining and quarrying and even basic metal smelting industry) as well as transformation of business field from agricultural sector to industrial sector, creative service industry and trade. Keywords: Transmigration Area, New Urban Industrial Zone, Strategic Area Growing Fast.